Impact of Temperature Variation on Calcium Profiling in a Neuronal Cell Due to Cancer: A Steady-State Case - Patil, Jayashree; Vaze, Ashwini; Sharma, Leena; Bachhav, Amol (Communications in Mathematics and Applications, 2023)
A crucially vital second messenger for intracellular signaling in the nervous system is Calcium. It regulates the release of synaptic transmitters. The cellular metabolism is monitored by diffusion, the activity of buffering, and influx in the cytoplasm. The temperature of the cellular microenvironment rises as excess energy from cellular metabolism is transformed into heat. The addition of medications or other cancer-curing treatments leads cancer cells to heat up more than normal cells, according to numerous studies. The calcium concentration profile is impacted by the cellular metabolism’s elevated temperature. This research aims to examine calcium profiles in neurons brought on by temperature changes brought on by cancer treatment. When there is calcium current input, the Goldman-Hodgkin-Katz (GHK) current equation and mathematical modelling are employed to determine calcium diffusion in neuron cells. Also, the impact of the temperature of the cellular environment on calcium concentration is studied. This model has been proposed for a 1-D steady-state case with the right initial and boundary conditions. To obtain the solution, the finite element method has been used. The simulations have been used to identify the effect of buffers as well as the effect of temperature variation on calcium distribution.